2022
DOI: 10.5194/bg-19-3739-2022
|View full text |Cite
|
Sign up to set email alerts
|

Variability and uncertainty in flux-site-scale net ecosystem exchange simulations based on machine learning and remote sensing: a systematic evaluation

Abstract: Abstract. Net ecosystem exchange (NEE) is an important indicator of carbon cycling in terrestrial ecosystems. Many previous studies have combined flux observations and meteorological, biophysical, and ancillary predictors using machine learning to simulate the site-scale NEE. However, systematic evaluation of the performance of such models is limited. Therefore, we performed a meta-analysis of these NEE simulations. A total of 40 such studies and 178 model records were included. The impacts of various features… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…In the above meta-analysis of the models, we found that water flux simulations based on EC observations can achieve high accuracy but also have high uncertainty through the modeling workflow. The R-squared of many water flux simulation models exceeds 0.8, possibly higher than some remotesensing-based and process-based models and possibly higher than carbon flux simulations such as the net ecosystem exchange (NEE) in a similar modeling framework (Shi et al, 2022). This may be because many data on important variables affecting carbon flux such as soil and biomass pools, disturbances, ecosystem age, management activities, and land use history are not yet effectively and continuously measured (Jung et al, 2011) with the global spatially and temporally explicit information.…”
Section: Opportunities and Challenges In The Water Flux Simulationmentioning
confidence: 97%
See 2 more Smart Citations
“…In the above meta-analysis of the models, we found that water flux simulations based on EC observations can achieve high accuracy but also have high uncertainty through the modeling workflow. The R-squared of many water flux simulation models exceeds 0.8, possibly higher than some remotesensing-based and process-based models and possibly higher than carbon flux simulations such as the net ecosystem exchange (NEE) in a similar modeling framework (Shi et al, 2022). This may be because many data on important variables affecting carbon flux such as soil and biomass pools, disturbances, ecosystem age, management activities, and land use history are not yet effectively and continuously measured (Jung et al, 2011) with the global spatially and temporally explicit information.…”
Section: Opportunities and Challenges In The Water Flux Simulationmentioning
confidence: 97%
“…In general, predictors related to meteorological, vegetation, and soil conditions were common to both ET and NEE simulations in a similar framework (Shi et al, 2022). However, in NEE predictions, explanatory variables such as soil organic content, photosynthetic photon flux density, and growing degree days (Shi et al, 2022) are not necessary for ET predictions. The selection of these variables requires our prior knowledge of the dominant drivers of ET and NEE anomalies of particular ecosystems and their differences.…”
Section: Differences From Nee Predictions In the Similar Model Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…When applied in regional or global extrapolation, it lacks a validation of the simulation results at regions without flux stations. More widely distributed meteorological stations have the potential to deliver more reliable NEE datasets to offset the limitation of the NEE validation in regions without flux stations (Shi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For example, eddy-covariance flux tower observations (Baldocchi, 2014) for carbon flux (i.e., net ecosystem exchange (NEE)) and water flux (i.e., evapotranspiration (ET)) have been widely used to investigate changes in ecosystem functions and their responses to climate change, vegetation condition changes, etc (Jung et al, 2020(Jung et al, , 2010Migliavacca et al, 2021;Peaucelle et al, 2019). With the increase in such observations, various statistical analysis methods such as emerging machine learning (Barnes et al, 2021;Migliavacca et al, 2021;Reichstein et al, 2019;Shi et al, 2022bShi et al, , a, 2020bTramontana et al, 2016) have been used to mine the hidden information on the effects of climate change and its induced changes in vegetation, etc. on ecosystem function variables such as carbon and water flux, which has not been understood in depth by process-based models (e.g., biogeochemistry models (Sakschewski et al, 2016)).…”
Section: Introductionmentioning
confidence: 99%